Incentives for clinical trials - Erik Grönqvist; Douglas Lundin (Stockholm School of Economics, The Economic Research Institute (EFI), 2006)
Who gains from more information on the quality of pharmaceutical drugs? Are there incentives for voluntary post-approval clinical trials among pharmaceutical companies? Contrary to popular belief, this paper shows that it is not in the consumer interest that clinical evidence establishing the relative effectiveness within a class of drugs are produced. Pharmaceutical companies, on the other hand, do benefit: the elimination of uncertainty regarding quality increases expected product differentiation, thereby raising prices for both high-quality and low-quality drugs, to the disadvantage of consumers. Still there is no unique equilibrium where the market provides clinical trials. If the costs of carrying out clinical trials are small, in relative terms, there will be a coordination problem between firms, as firms will want a rival firm to carry the cost. If the costs are large they will be prohibitive. Legislation that obligates entering firms to carry out post-approval trials is beneficial for firms if it solves the coordination problem, but is otherwise harmful. Legislation is never in the interest of consumers.
Keywords: D81; D83; I18; L15; 330; Quality uncertainty; Symmetric information; Pharmaceutical market; Clinical trials; Pharmazeutisches Produkt; Anreizregulierung; Produktqualität; Preisniveau; Theorie; Pharmazeutische Forschung